Photoelectric sensors for wireless monitoring of bridge scour - laboratory investigation and field validation - Farooq, Mohammed; Azhari, Fae; Banthia, Nemkumar (Structure and infrastructure engineering, 2025)
Scour, or the erosion of bed material is a major cause of bridge failure across the world. Monitoring scour levels at bridge foundations reduces the risk of failure through timely condition-based maintenance. This paper evaluates the use of photoelectric sensors for scour detection through laboratory studies and subsequent field investigation. Two types of photoelectric sensors, namely diffusive-reflective and through-beam, were independently investigated. The sensors were installed at six distinct depths on a simulated bridge pier in a laboratory flume. Scour resulting from hydrodynamic action triggered the sensors at different levels, enabling scour depth detection. An inverse response from the sensors detected scour refill. Following successful laboratory tests, a photoelectric scour-sensing prototype was installed in a small creek in August 2019 which continued to monitor scour until April 2022. The prototype response confirmed laboratory results and continues to perform well under various field conditions such as rain, debris, and snow. The very low-cost system required minimal power and bandwidth, and the sensing component was robust to flow parameters. Long-term field studies are required to evaluate their susceptibility to biofouling and develop biofouling countermeasures.